Trace glucose and lipid metabolism in high androgen and high-fat diet induced polycystic ovary syndrome rats - Zhai Hua-Ling; Wu Hui; Xu Hui; Weng Pan; Xia Fang-Zhen; Chen Yi; Lu Ying-Li (BMC, 2012)
Abstract Background There is a high prevalence of diabetes mellitus (DM) and dyslipidemia in women with polycystic ovary syndrome (PCOS). The purpose of this study was to investigate the role of different metabolic pathways in the development of diabetes mellitus in high-androgen female mice fed with a high-fat diet. Methods Female Sprague-Dawley rats were divided into 3 groups: the control group(C), n = 10; the andronate-treated group (Andronate), n = 10 (treated with andronate, 1 mg/100 g body weight/day for 8 weeks); and the andronate-treated and high-fat diet group (Andronate+HFD), n = 10. The rate of glucose appearance (Ra of glucose), gluconeogenesis (GNG), and the rate of glycerol appearance (Ra of glycerol) were assessed with a stable isotope tracer. The serum sex hormone levels, insulin levels, glucose concentration, and the lipid profile were also measured. Results Compared with control group, both andronate-treated groups exhibited obesity with higher insulin concentrations (P < 0.05) but similar blood glucose concentrations. Of the two andronate-treated groups, the andronate+HFD group had the most serious insulin resistance (IR). Estrus cycles were completely acyclic, with polycystic ovaries and elevated serum lipid profiles in the andronate+HFD group (P < 0.05). Ra of glucose and GNG increased significantly in the andronate+HFD rats. However, the Ra of glycerol was similar in the three groups. Conclusions Andronate with HFD rat model showed ovarian and metabolic features of PCOS, significant increase in glucose Ra, GNG, and lipid profiles, as well as normal blood glucose levels. Therefore, aberrant IR, increased glucose Ra, GNG, and lipid metabolism may represent the early-stage of glucose and lipid kinetics disorder, thereby might be used as potential early-stage treatment targets for PCOS.